(untitled) - Michael James Hill (1937- (Cambridge, Massachusetts, 1993)
The book brings up to date all the relevant information and reflects the new views of social policy in Britain. Taking full account of the dramatic changes in social policy made by the Conservatives under Mrs. Thatcher and inherited by John Major, this book provides an essential guide to British social policy as it is today. Developments such as the 1986 Social Security Act, privatization, increased unemployment and the 'community care' debate are fully covered, as are effects of over a decade of Conservative policy making: on housing, education and the personal social services in particular
Keywords: great britain - social policy,welfare economics,welfare state